Surgical exposure dan perawatan ortodontik pada impaksi gigi insisif sentral rahang atas (Surgical exposure and orthodontic treatment on labially impacted maxillary central incisor) - Bingah Fitri Melati; Teguh Budi Wibowo; Betadion Rizki (Dental Journal (Majalah Kedokteran Gigi), 2014)
Background: As a clinician we have to concern for an unerupted teeth especially in mixed dentition. Eruption failure can also be caused by early loss of deciduous teeth. Purpose: To report a case of unerupted maxillary central incisor caused by early loss of deciduous teeth due to trauma and the combination of excisional and orthodontic treatment. Case: A 8-years-old girl in mixed dentition phase came to Universitas Airlangga Dental Hospital with chief complaint of unerupted right maxillary central incisor while the left central incisor and both lateral incisor had erupted already. She had trauma when she was 1 year old and loss mostly her primary maxillary central incisors. An intraoral examination revealed lack of space in #11 region with root retained of #51, bulge was palpated in vestibulum and periapical radiograph showed that a delayed eruption upper central incisor without presence of disturbance. Case management: The exposure of the tooth was under local anesthesia a year after the orthodontic performed to make enough space for traction the tooth. A button was placed at palatal and used elastic strait to traction the tooth. After 3 months, bracket placed at labial to positioning until leveled and aligned with adjacent teeth. Conclusion: A simple excisional and orthodontic treatment were succesfully treated the labially impacted teeth.Latar belakang: Sebagai seorang klinisi kita harus memperhatikan apabila terdapat gigi yang belum erupsi terutama pada fase gigi pergantian. Kegagalan erupsi gigi juga dapat disebabkan karena tanggal premature gigi sulung. Tujuan: Melaporkan kasus impaksi gigi insisif sentral rahang atas yang disebabkan kehilangan premature gigi sulung karena trauma dengan kombinasi eksisi sederhana dan perawatan ortodontik. Kasus: Anak perempuan usia 8 tahun pada fase gigi pergantian datang ke Rumah Sakit Gigi dan Mulut Universitas Airlangga dengan keluhan gigi insisif sentral kanan rahang atasnya (#11) belum erupsi meskipun gigi insisif sentral kiri #21 dan kedua insisif lateralnya #22 sudah erupsi. Pasien tersebut pernah terjatuh saat masih usia 1 tahun dan hampir kehilangan seluruh gigi sulung insisif sentral rahang atasnya. Pada pemeriksaan klinis tampak ruang yang sempit pada region #11 dan terdapat sisa akar gigi #51, jaringan keras teraba pada palpasi daerah vestibulum dan pemeriksaan radiografi periapikal tampak impaksi gigi insisif sentral rahang atas tanpa adanya penghalang. Tatalaksana kasus: Exposure gigi dilakukan dibawah anestesi lokal 1 tahun setelah perawatan ortodontik untuk membuka space bagi #11. Button diletakkan di palatal gigi 11 dan digunakan elastic strait untuk traksi gigi tersebut. Setelah 4 bulan bracket dipasang untuk memposisikan gigi pada lengkung yang benar. Simpulan: Teknik eksisi sederhana dan perawatan ortodontik berhasil merawat gigi impaksi yang terletak di labial.